Embarazo gemelar: aspectos epidemiológicos hospital de apoyo III integrado Tarapoto (1968- 1989) - Vega Celis, Manuela Aurora (1991)
In women, pregnancy of a product is how normal conception as well corresponds The structure f unction of U uterus so that multiple pregnancy can be considered as an alteration of normal, perhaps as a border between the physiological process and pathological (1.2}. It is difficult to establish the exact incidence of twin pregnancies and many of the statistical (epidemiological) studies of twins, exclude couples whose products died at birth or before. By eliminating thus stillbirths and spontaneous abortions, incidence rates reflect pregnancies that have come to fruition in advanced gestational ages and the simple conception of twins. Also, it has been shown that twin pregnancies have an increased frequency of spontaneous abortion, pregnancy single product (2.3) as another possibility, can only lost one fetus become known as the phenomenon of "vanishing twin" (4 ). In humans there are two main types of twins, identical twins or momocigóticos resulting from the fertilization of an egg and fraternal or dizygotic twins, who come from multiple ovulation in the subsequent two eggs fertilized by different sperm. Family studies confirm that apparently only dizygotic generality is hereditary, suggesting that monozygotic twins are the result of a casual teratogenic phenomenon (5-9). It is proved that the frequency of multiple births in humans is influenced by race, heritage, parity and maternal age (5) with respect to dizygotic twins because monozygotic appear with the same frequency and is considered independent of those four factors (5). Many authors (1-5,10-19) have reported that the twin pregnancy carries a high morbidity and perinatal mortality increased frequency of malformations; cord accidents, intergemelar transfusion syndrome, intrauterine growth retardation, preterm births that are considered leading cause of obstetric trauma complications during delivery. The woman with twins also has a higher rate of complications and death. First, the rate of spontaneous abortions is more frequent (1-3), excessive nausea and vomiting anemia, preeclampsia, proteinuria is five times higher in twins than in single fetus; polyhydramnios that contributes to premature rupture of membranes and preterm delivery; have an increased risk of bleeding, the danger is in the uterine atomie and postpartum hemorrhage that result from the sudden decomposition of the uterus with excessive distension, finally the risk that arises most often by surgery (desárea) and with them the complications arising from the operation (6, 12, 20, 21); this set of factors makes women at high risk (22,23) is considered. As indicated determines that the goal key clinical is to prevent the premature and intrauterine growth retardation so that assistance has been directed towards a proper diet of pregnant, prenatal every two weeks at the beginning, I sleep early in bed before 28 weeks , prophylactic tocolysis, cervical cerclage, monitoring, fetal by biochemical tests and serial studies of ecosonography. On the other hand some of the problems of mortality and morbidity in twin pregnancies are attributable to late diagnosis or the failure to diagnose the presence of a second fetus before birth (24). The most suitable diagnostic method is ecosonography (25 - 27. 28), but never insist on the great clinical importance of considering throughout pregnancy, the possibility of twins. Another diagnostic method increases the sensitivity of diagnosing twin pregnancy are Alfa - fetoprotein and human placental lactogen level (29). Regarding the decision to the attention of twin births may depend on the presentation of the twins, knowing that pregnancy Gemelar have a higher incidence of dysfunctional labor, likewise, developments and both maternal and fetal conditions (6). The high maternal and fetal morbidity and mortality are described in twin pregnancy have prompted conduct this research study in order to know its incidence and associated epidemiological, preparing the national bibliographic little availability.